Naturalizing Disaster in Media Discourse: A Critical Discourse Analysis of the Sibolga Landslide Coverage on Kompas TV - Dwi Angeli Pardede; Isabel Selmiola Sabrina; Bella Sonia Sianturi; Partohap Saut Raja Sihombing (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Disaster discourse in Indonesian media often emphasizes natural factors while marginalizing structural causes, thereby depoliticizing complex socio-environmental issues. This study investigates the discursive construction of the Sibolga landslide as represented in the Kompas TV news article